Mobile user location prediction enabled services in ubiquitous computing: determination user location using MFN algorithm - Mantoro, Teddy; Olowolayemo, Akeem Koye (2009)
The past decade has seen a rapid development of many applications in the field of pervasive or ubiquitous computing. This is made possible by rapid development in mobile and handheld devices. Due to this widespread usage however, localization and positioning systems, especially indoor, have become increasingly important for resources management. This entails information devices to have context awareness and prediction of current location of the users to adequately respond to the need at the time. In this work, we examine the location determination techniques by attempting to predict location of mobile users taking advantage of signal strength (SS) and signal quality (SQ).